Studi Medan Elektromagnetik Pada Efek Radiasi Elektromagnetik Dari Saluran Udara Tegangan Ekstra Tinggi (SUTET) Untuk Kesehatan Manusia - Muhammad Abdullah Bin Matni; Vinta Retriani; Raihan Raihan; Alifia Nurfadilah; Diyajeng Luluk Karlina (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
This study examines the impact of electromagnetic radiation exposure from Extra High Voltage Overhead Transmission Lines (EHV OTL) on human health in the Banten region, Indonesia. SUTET, which operates at a voltage of 500 kV, generates an electromagnetic field that can affect the health of the surrounding community. The research was conducted through in-depth interviews with 30 respondents, consisting of residents around the SUTET, medical personnel, and health experts. The interview results showed that 70% of respondents were concerned about the health impacts of SUTET, with the most common complaints including headaches (45%), sleep disturbances (30%), and chronic fatigue (25%). In addition, the majority of respondents felt they did not receive sufficient information regarding the safe exposure limits to electromagnetic fields. Nevertheless, the public's knowledge about the long-term effects of electromagnetic fields is still limited. The thematic analysis found a gap in information between the public and existing regulations. This research implies the need for better educational measures from the government and related institutions regarding the dangers of SUTET and electromagnetic radiation. Furthermore, it is recommended that further research be conducted to establish safe exposure limits to electromagnetic fields in Indonesia, as well as to formulate more effective policies to protect public health around SUTET transmission lines.